Plant growth-promoting bacteria (PGPB) inoculants enhance the bacterial network connectivity more than non-PGPB in heavy metal-contaminated soil - Kong, Zhaoyu; He, Yong; Xue, Jiaxiang; Chen, Zhaohao; Gui, Yongqi; Wu, Jiahao; Chen, Xiaomeng (Frontiers in Plant Science, 2025)
Optimizing the performance of plant growth-promoting bacteria (PGPB) inoculants in phytoremediation requires a deeper understanding of their interactions with the indigenous soil microbiome. However, current knowledge is particularly limited regarding how PGPB versus non-PGPB inoculants interact with indigenous microbes and establish colonization persistence in the rhizosphere. In this study, we employed amplicon sequencing to compare the impacts of PGPB versus non-PGPB inoculants on the indigenous rhizosphere and bulk soil microbiome of Indian mustard in heavy metal-contaminated soil, and their interactions within the indigenous bacterial networks. Our results showed that both PGPB and non-PGPB inoculants significantly altered the composition and diversity of the rhizosphere microbiome. However, only PGPB inoculants enhanced the complexity and stability of bacterial co-occurrence networks. PGPB inoculants not only maintained rhizosphere persistence but also actively integrated into the network, enhancing associations with indigenous bacterial taxa. Notably, they established enhanced co-occurrence associations with native bacterial taxa characterized as potential PGPB, including Lysinimonas, Sinomonas, Nocardioides, Actinoalloteichus, Amycolatopsis, Bradyrhizobium, Novosphingobium etc., and these interactions were predominantly positive. These findings highlight the important role of PGPB versus non-PGPB inoculants in reshaping the rhizosphere microbiome under heavy metal stress, indicating a potential approach for improving phytoremediation efficiency by fostering a more resilient and cooperative soil microbiome.